Matrix Corrected SIMS In Situ Oxygen Isotope Analyses of Marine Shell Aragonite for High Resolution Seawater Temperature Reconstructions - Oliver M. Medd; Laura M. Otter; Ian S. Williams; Richard A. Stern; Michael W. Förster; Stephen M. Eggins; Laura Rodriguez‐Sanz; Nerilie J. Abram; Miaohong He; Michael J. Ellwood; Jessica A. Hargreaves; Stewart J. Fallon; et al. (Geochemistry, Geophysics, Geosystems)
Abstract Marine shells incorporate oxygen isotope signatures during growth, creating valuable records of seawater temperature and marine oxygen isotopic compositions. Secondary ion mass spectrometry (SIMS) measures these compositions in situ at finer length‐scales than traditional stable isotope analyses. However, determining oxygen isotope ratios in aragonite, the most common shell mineral, is hampered by a lack of ideal reference materials, limiting the accuracy of SIMS‐based seawater temperature reconstructions. Here, we tested the capability of SIMS to produce seawater temperature reconstructions despite the matrix calibration challenges associated with aragonite. We cultured Anadara trapezia bivalves at four controlled seawater temperatures (13–28°C) and used strontium labeling to mark the start of the temperature‐controlled shell increment, allowing for more spatially precise SIMS analysis. An improved matrix calibration was developed to ensure more accurate bio‐aragonite analyses that addressed matrix differences between the pure abiotic reference materials and the bio‐aragonite samples with intricate mineral‐organic architectures and distinct minor and trace element compositions. We regressed SIMS‐IRMS biases of abiotic and biogenic aragonites that account for their systematic differences in major, minor, and trace elements, allowing for more accurate SIMS analyses of the temperature‐controlled shell increment. The thorough matrix calibration allowed us to provide a SIMS‐based seawater‐corrected oxygen isotope thermometer of T(°C) = 23.05 ± 0.36 − 4.48 · (δ18Oaragonite [‰ VPDB] − δ18Oseawater [‰ VSMOW] ± 0.25) and 103lnαaragonite‐seawater = (17.78 ± 0.88) · 103/T (K) − (29.44 ± 2.40) that agrees with existing aragonitic IRMS‐based thermometer relationships and improves the applicability of SIMS‐based paleo‐environmental reconstructions of marine bio‐aragonites.